2016
DOI: 10.1111/apps.12082
|View full text |Cite
|
Sign up to set email alerts
|

Crafting your Career: How Career Competencies Relate to Career Success via Job Crafting

Abstract: This study aimed to investigate whether career competencies could enhance an employees subjective career success in terms of perceived employability and work-home balance via job crafting behaviors. Based on Job Demands-Resources (JD-R) Theory, we examined a potential motivational process in which career competencies, as a personal resource, would enhance career success through expansive job crafting. The results showed that job crafting mediated the positive relationship between career competencies and both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
314
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 290 publications
(359 citation statements)
references
References 66 publications
(120 reference statements)
30
314
0
15
Order By: Relevance
“…Approach crafting also benefits individuals' career, presumably because employees are able to develop their personal resources through increased learning opportunities or to translate already existing resources into other valuable assets (Kira, van Eijnatten, & Balkin, ). Empirical studies have supported that approach crafting predicts one's perceived employability (Brenninkmeijer & Hekkert‐Koning, ), career competence (Akkermans & Tims, ), career satisfaction and commitment (Kim & Beehr, ), and objective promotions (Cenciotti, Alessandri, & Borgogni, ).…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
“…Approach crafting also benefits individuals' career, presumably because employees are able to develop their personal resources through increased learning opportunities or to translate already existing resources into other valuable assets (Kira, van Eijnatten, & Balkin, ). Empirical studies have supported that approach crafting predicts one's perceived employability (Brenninkmeijer & Hekkert‐Koning, ), career competence (Akkermans & Tims, ), career satisfaction and commitment (Kim & Beehr, ), and objective promotions (Cenciotti, Alessandri, & Borgogni, ).…”
Section: A Synthesized Nomological Network Of Antecedents and Consequmentioning
confidence: 99%
“…As we have argued throughout this article, it is the interplay between agency and context that enables us to more fully understand contemporary career processes. In this case, it would be highly interesting to, for example, study the interaction between career shocks and career self-management behaviours (King, 2004) and career crafting (Akkermans & Tims, 2017). In addition, it would be important to research whether certain individuals are more at risk of developing adverse reactions to shocks than others and whether individuals can be inoculated against negative career shocks, that is, whether people might prepare for and become more resilient in the face of career shocks (cf.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…For example, both social cognitive career theory (Lent et al, 1994) and career construction theory (Savickas, 2005) -two of the most frequently cited career theories in recent years -are premised on the notion of preparing for decision-making and acting upon those preparations via goaldirected behaviours. Empirical research has closely followed this trend, as evidenced by an emphasis on topics such as career self-management (King, 2004), proactive career behaviours (De Vos, De Clippeleer, & Dewilde, 2009), career crafting (Akkermans & Tims, 2017) and employability (Forrier, Verbruggen, & De Cuyper, 2015;Van der Heijde & Van der Heijden, 2006). Indeed, a recent review of papers published between 2012 and 2016 in four leading career journals showed that career decision-making, career mobility, career capital, employability and proactive career behaviours are among the most popular topics in the recent careers literature (Akkermans & Kubasch, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…Individuals who have resources look for resourceful settings, and these settings then enable them to accumulate more resources. For example, employees who feel employable may actively pursue high quality jobs and then craft those jobs to become even more resourceful (Akkermans & Tims, ). In contrast, individuals with fewer resources are inclined to defend existing resources, even to the extent that they may not be perceptive for opportunities because this implies risking scarce resources.…”
Section: Employability: Blind Spotsmentioning
confidence: 99%